2023
DOI: 10.1101/2023.04.26.538461
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HIV-1 infection of genetically engineered iPSC-derived central nervous system-engrafted microglia in a humanized mouse model

Abstract: The central nervous system (CNS) is a major human immunodeficiency virus type 1 reservoir. Microglia are the primary target cell of HIV-1 infection in the CNS. Current models have not allowed the precise molecular pathways of acute and chronic CNS microglial infection to be tested with in vivo genetic methods. Here, we describe a novel humanized mouse model utilizing human-induced pluripotent stem cell-derived microglia to xenograft into murine hosts. These mice are additionally engrafted with human peripheral… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 91 publications
0
1
0
Order By: Relevance
“…Moreover, these infected microglia have been effectively cocultured in various model systems, including human stem cell-derived neural tricultures, 14 , 50 primary neuron progenitor cell-derived organoids, 51 iPSC-derived cerebral organoids, 52 and a humanized mouse model. 53 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these infected microglia have been effectively cocultured in various model systems, including human stem cell-derived neural tricultures, 14 , 50 primary neuron progenitor cell-derived organoids, 51 iPSC-derived cerebral organoids, 52 and a humanized mouse model. 53 …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the feasibility of infecting iPSC-derived macrophages (Vaughan-Jackson et al 2021) and microglia (Rai et al 2020) with HIV-1. Moreover, these infected microglia have been effectively cocultured in various model systems, including human stem cell derived neural tricultures (Alvarez-Carbonell et al 2020;Ryan et al 2020), primary neuron progenitor cell derived organoids (dos Reis et al 2020), iPSC-derived cerebral organoids (Gumbs et al 2022), and a humanized mouse model (Min et al 2023).…”
Section: Introductionmentioning
confidence: 99%